First Impressions: The Case of Teacher Racial Bias - Marcos A. Rangel; Ying Shi (Institute of Labor Economics (IZA), 2020)
We study racial bias and the persistence of first impressions in the context of education. Teachers who begin their careers in classrooms with large black-white score gaps carry negative views into evaluations of future cohorts of black students. Our evidence is based on novel data on blind evaluations and non-blind public school teacher assessments of fourth and fifth graders in North Carolina. Negative first impressions lead teachers to be significantly less likely to over-rate but not more likely to under-rate black students' math and reading skills relative to their white classmates. Teachers' perceptions are sensitive to the lowest-performing black students in early classrooms, but non-responsive to highest-performing ones. This is consistent with the operation of confirmatory biases. Since teacher expectations can shape grading patterns and sorting into academic tracks as well as students' own beliefs and behaviors, these findings suggest that novice teacher initial experiences may contribute to the persistence of racial gaps in educational achievement and attainment.
Keywords: I24; J15; 330; racial bias; first impressions; teachers; racial disparities